Rancang Bangun Dashboard Monitoring Data Center Infrastructure Management (Dcim) Yang Terintegrasi Grafana Alert Dan Bot Telegram Dengan Arsitektur Kubernetes Studi Kasus Pt. Pelayaran Nasional Indonesia (Pelni) - Nadhira, Inaz; Iqbal, Muhammad; Putra, Chandra Mahendra (eProceedings of Applied Science, 2024)
This final project aims to develop an integrated monitoring system for Data Center Infrastructure Management (DCIM) applications in a Kubernetes environment. The system uses Prometheus to display metrics, Grafana for data visualization, as well as Grafana Alerts and Telegram bot for real-time notifications. Research methods include needs analysis, grafana dashboard design, prometheus configuration, customization of grafana alerts, and integration with telegram bots. Testing and validation are carried out to ensure functionality before system implementation. Routine maintenance and system upgrades are performed to ensure optimal performance. This monitoring system can provide effective monitoring and fast notifications, improve the performance and availability of DCIM applications, and help organizations identify and handle problems more quickly and efficiently.